Tradução para língua estrangeira - Branco, Vânia Patrícia da Silva (2017)
This report consists of translating, to English, an excerpt of the book “As Pupilas do Senhor Reitor”, written originally in Portuguese by Júlio Dinis. It begins with a thorough examination of the author’s life and work. Then, the specific characteristics of the author’s style are studied. In the second chapter, the translator presents her choices, which are always justified. Finally, inverse translation’s advantages are outlined.